1994
DOI: 10.1084/jem.179.2.651
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide in the pathogenesis of spontaneous murine autoimmune disease: increased nitric oxide production and nitric oxide synthase expression in MRL-lpr/lpr mice, and reduction of spontaneous glomerulonephritis and arthritis by orally administered NG-monomethyl-L-arginine.

Abstract: Summary MRL-I/r/I/rHowever, the chromosomal location of the NOS gene was consistent with an insulin-dependent diabetes locus identified in an analysis of nonobese diabetic (NOD) mice. These results suggest that elevated nitric oxide production could be important in the pathogenesis of autoimmunity, and that treatments to block the production of nitric oxide or block its effects might be valuable therapeutically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
252
0
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(269 citation statements)
references
References 58 publications
(67 reference statements)
14
252
0
3
Order By: Relevance
“…After incubation, culture supernatants were collected and used for an NO assay. NO formation was determined as the stable production of nitrite (NO 2 -) in culture supernatants using Griess reagent [53].…”
Section: No Assaymentioning
confidence: 99%
“…After incubation, culture supernatants were collected and used for an NO assay. NO formation was determined as the stable production of nitrite (NO 2 -) in culture supernatants using Griess reagent [53].…”
Section: No Assaymentioning
confidence: 99%
“…Increased levels could merely reflect underlying inflammation. Nevertheless, there is increased production of NO during the course of the murine MRL/lpr and NZB/W models of lupus and in human SLE (265)(266)(267). Moreover, elevated levels of endothelial cell iNOS, serum nitrite and peroxynitrite levels correlate with measures of disease activity and titers of dsDNA antibodies (267,268).…”
Section: Nitric Oxide and Inducible Nitric Oxide Synthasementioning
confidence: 99%
“…In addition to glomerulonephritis, MRL-lpr mice also develop arthritis, vasculitis, and lymphoproliferation (18). We previously demonstrated that spontaneous immune complex glomerulonephritis and arthritis in MRL-lpr mice was significantly decreased by NMMA administration early in disease (19). These mice were given an arginine-free diet to prevent arginine from competitively inhibiting NMMA uptake in macrophages (20).…”
Section: Introductionmentioning
confidence: 99%
“…These mice were given an arginine-free diet to prevent arginine from competitively inhibiting NMMA uptake in macrophages (20). Control MRL-lpr mice in these experiments, on the arginine-free diet, developed less pathologic disease than historical controls, suggesting dietary arginine restriction alone may alter disease expression (19).…”
Section: Introductionmentioning
confidence: 99%